Teaching students about death and other losses - Veronika, Doris; Arambašić, Lidija (Croatian regional development journal, 2021)
The purpose of this research is to investigate the extent to which the preconditions for the introduction of topics on death and other losses are met in primary schools. The aim was to examine the beliefs of primary school staff about teaching students on these topics and to examine their knowledge of the grieving process in children and youth. The sample consisted of 213 school staff from 13 primary schools in Zagreb and the surrounding area who met the and the . In this paper, the results of this empirical research are presented, which showed that primary school teachers have beliefs about higher self-competence for teaching students on the mentioned topics in relation to subject teachers. The results also showed the existence of a low positive correlation between beliefs about the usefulness of teaching about death and other losses and knowledge about the process of grieving children and young people. A low negative correlation was also found between the age of the participants and the results of the Knowledge Test. The conducted research brings practical implications that are important for further consideration of this topic and for the design of education for teachers and professional associates on the topic of grieving processes in children and youth.